Stochastic control in insurance - Schmidli, Hanspeter (Probability and its applications., 2007)
Provides an introduction to stochastic control techniques, both in discrete and continuous time. This book applies the principles to several problems in actuarial mathematics which show how verification theorems and existence theorems may be proved. It is suitable for graduate and postgraduate students of actuarial and financial mathematics.